Litenum Game: Impact to the Literacy and Numeracy Performance of Grade One Pupils - DE RAMOS, MALOU (International Journal of Arts, Sciences and Education, 2022)
ABSTRACT PURPOSE. This research study was undertaken to determine the impact of Litenum Game in the literacy and numeracy performance of grade one pupils in San Antonio Central School, S.Y. 2021 -2022. RESEARCH PROBLEM. What is the impact of Litenum Game to the Literacy and Numeracy Performance of Grade One Pupils in San Antonio Central School? METHODOLOGY. To achieve the purpose of the study, quasi-experimental method was used to measure the performance of grade one pupils in literacy and numeracy before and after the use of Litenum Game. CONCLUSIONS. Based from the gathered data, there is a significant difference in the performance of grade one pupils before and after using Litenum Game. Thus, Litenum Game is an effective way of acquiring basic literacy and numeracy skills. SIGNIFICANCE. This research project provided significant data on pre-test and post test result of the pupils’ literacy and numeracy performance. Litenum Game has a distinct contribution in improving pupils’ performance in basic literacy and numeracy. Keywords: Litenum Game, Literacy and Numeracy Performance